Democracy and governance in Africa : conclusions and papers presented at a conference of the Africa Leadership Forum : 29 November-1 December 1991, Ota, Nigeria - Africa Leadership Forum; Africa Leadership Forum ([S.l.] : Africa Leadership Forum, 1991)
This publication is a summary of papers presented at the African Leadership Forum to examine the nature and forms of the current wave of pro-democracy movement that was sweeping through most parts of Sub- Saharan Africa to allow for relevant lessons and experience.
Includes bibliographical references.
gp. 25/01/2019
Loan
Keywords: Democracy; Politics and governent; Africa